Answer:
<u>11098 cm³</u>
Step-by-step explanation:
<u>Volume of top prism</u>
- V = 62 x 3 x (13 - 7)
- V = 186 x 6
- V = 1116 cm³
<u>Volume of bottom prism</u>
- V = 62 x 23 x 7
- V = 1426 x 7
- V = 9982 cm³
⇒ Total volume = Volume (top) + Volume (bottom)
⇒ Total volume = 1116 + 9982
⇒ Total volume = <u>11098 cm³</u>
Answer:
The image is not loading!!
Step-by-step explanation:
Re-upload the question so maybe I can see it.
Answer: It equals 8.
Step-by-step explanation:
Answer:
0,11
Step-by-step explanation:
y^2-11y=0
y(y-11)=0 we have transformed the equation into a product
a product can be zero only if one of the factors is 0
so the two solutions are
y=0
and y-11=0 y=11
Answer:
n = - ![\frac{4}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B7%7D)
Step-by-step explanation:
Given
(1 + n) = -
n
Multiply both sides by 6 ( the LCM of 3 and 2 ) to clear the fractions
4(1 + n) = - 3n ← distribute left side
4 + 4n = - 3n ( add 3n to both sides )
4 + 7n = 0 ( subtract 4 from both sides )
7n = - 4 ( divide both sides by 7 )
n = - ![\frac{4}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B7%7D)